The Cordon Sanitaire - Kadri, Ali. author. aut Link
XVII, 170 p.
Keywords: This work compares the development experiences of East Asia and the Arab world. It posits that in view of the collapse in socialism and its ideological retreat, their development performances are intensely over determined by their modes of integration with world capital. For East Asia, it's through manufacturing of civilian-end use commodities and for the Arab World, through militarism. The book is a unique attempt approaching the topic from the theoretical angle using an analytical comparative perspective.